Rekabentuk peranti pemisah-gabung optik 2x3 berasaskan pandu gelombang planar - Mohammad Syuhaimi Ab-Rahman,; Norazilawati Md-Zain,; Siti Rahayu Hassan,; Kasmiran Jumari, (2009)
In this paper, we present the design of 2x3 optical splitter-combine based on waveguide with SU-8 polymer material. The technology ensures low cost fabrication and excellent performance as compared to conventional technique that uses fused coupler for optical splitter fabrication. The optical splitter-combine is suggested to be used in passive customer access network FTTH-PON to variety the signals send to the premises. It is the first time reported. The problems arose such as the loss of output power is also discussed. The simulation result shows that various factors; namely the width of waveguide, refractive index and wide-angle branching will increase the output power loss. To obtain maximum power, the optimization of those parameters’ value must be used. This designed optical splitter is operated at wavelength 1500 nm – 1600 nm. In this study, we characterized the trend of total output power with the effect of the parameters studied.